Drama from Modern Life: Unknown Play by Andrei Platonov (1939) - Maria V. Osipenko (Studia Litterarum)
For the first time, the publication introduces a multi-act play by A. Platonov, restored from the materials from two collections of the writer from the Moscow (Manuscript Department of the Institute of World Literature of the Russian Academy of Sciences) and St. Petersburg (Manuscript Department of the Institute of Russian Literature of the Russian Academy of Sciences) archives into scientific circulation. The play is not titled, not dated, not finished, and contains copious unfinished edits. The introductory article to the publication substantiates the dating of the play, indicates the close inclusion of the work in the context of the autumn of 1939, and traces some of the realities of 1939 reflected in the work.